IDENTIFIKASI ZAT WARNA RHODAMIN B PADA KOSMETIK PEMERAH PIPI DAN EYE SHADOW DENGAN METODE KLT DAN KCKT - Winasih Rachmawati (JURNAL FARMASI GALENIKA, 2014)
Rhodamine B is a synthetic red in paint and textile industry which is conclude as carcinogenic and being accumulated in the body. Cosmetics such as blush on and eye shadow is decorative cosmetics giving redish color and has a red color in the preparate. Identification of rhodamine B in blush on and eye shadow was conducted using TLC and HPLC. The mobile ammoniaï€ n-butanol ï€phase in TLC method was mixture of ethyl acetate 25% (20:55:25, v/v/v) with Rf value of 0.86. HPLC was then further used ï€to analyze at a wavelength 554 nm, using mobile phase acetonitrile water (47:47:6, v/v/v) with a flow rate of 1.4 mL/min and C18ï€methanol column. The limit of detection and limit of quantitation for rhodamin B were 0.449 and 1.498 Î¼g/mL, respectively. Three of six samples of blush on and all eye shadow samples positive containing rhodamine B. Keywords:, , , , . Kata kunci : ,